Jefferson's Poplar Forest : Unearthing a Virginia Plantation - Gary, Jack; Heath, Barbara J., 1960- (Book collections on Project MUSE., 2012)
This study investigates the plantation and the lives of the enslaved African and African American labourers residing at Poplar Forest, Thomas Jefferson's retreat home and working plantation, between the American Revolution and the Civil War. Contributors focus on archaeological investigations into Poplar Forest's agricultural and ornamental landscapes, the ceramics used by Jefferson at his private retreat, and the material, dietary, and social worlds of enslaved labourers.